Peningkatan Kepercayaan Diri Mahasiswa Calon Guru melalui Pembelajaran Berbasis Proyek Pengembangan Alat Peraga Edukatif - Firdiawan Ekaputra (Medan Resource Center, 2026)
Self-confidence is a fundamental affective competence that supports prospective teachers in communicating ideas, delivering presentations, and demonstrating professional capabilities during the learning process. However, many students in the Chemistry Education Program at the University of Jambi exhibit limited self-confidence, which may hinder their academic engagement and professional development. This study aimed to examine whether project-based learning centered on the development of educational aids could enhance the self-confidence of students enrolled in the Chemistry Education Workshop course. A quantitative approach employing a pre-experimental one-group pretest-posttest design was adopted. Data were collected from Chemistry Education students using a self-confidence questionnaire and analyzed through the Shapiro-Wilk normality test and a paired-samples t-test. The findings revealed a statistically significant improvement in students’ self-confidence following the implementation of project-based learning. Engaging students in designing and presenting educational aids fostered active participation, creativity, collaborative learning, and authentic problem-solving experiences that strengthened both their affective development and professional competencies. These findings suggest that project-based learning constitutes an effective pedagogical approach for enhancing self-confidence while simultaneously preparing prospective chemistry teachers for future instructional practice.